PREFERENCES IN ONLINE LEARNING OF STS: PERSPECTIVES FROM STUDENTS - Kimberly C. Rivera (Adisam Publisher, 2025)
In today's higher education setting, the integration of online learning has profoundly transformed pedagogical practices, particularly in Science, Technology, and Society (STS) education. This study investigates students' preferences for online learning in the context of STS at a state university in the Philippines. Using a researcher-developed questionnaire focused on Modality, Assessment, Relevance, and Interaction (MARIQ), the research examines various aspects of online learning methods and assessment practices. The study reveals that students prefer asynchronous learning modes and multimedia-rich content to enhance engagement and comprehension. These insights are vital for shaping curriculum design and instructional strategies, with an emphasis on the need for adaptable assessment methods and interactive learning platforms. Additionally, the study addresses challenges such as maintaining student engagement and improving technological competencies. It suggests potential areas for future research in adaptive technologies and innovative teaching approaches to further enhance STS education.